Determination of Heavy Metals and Pesticides in Different Types of Fish Samples Collected from Four Different Locations of Aegean and Marmara Sea - Tufan Topal; Canan Onac (Journal of Food Quality)
Heavy metals and pollutants cause serious damage to the ecological environment and accumulate in marine species in the seas. These pollutants and heavy metals accumulating in living species are a serious source of danger for human health. For this purpose, in this study, heavy metal (lead, mercury, copper, zinc, arsenic, cadmium, silver, manganese, and nickel) and pesticide (p-p′-DDE, α-BHC, endosulfan, endosulfan sulfate, endrin, aldrin, heptachlor, heptachlor epoxide, methoxychlor, p-p′-DDD, p-p′-DDT, β-BHC, cypermethrin, and dieldrin) analyses of four different fish species (Pomatomus saltatrix, Dicentrarchus labrax, Mugil cephalus, and Sparus aurata) collected from the Aegean and Marmara seas were carried out by gas chromatography-mass spectroscopy and using an inductively coupled plasma-mass spectrometer. We observed serious and remarkable arsenic, lead, and cadmium concentrations in the muscle meat of fish sample. p-p′-DDE and endosulfan were determined in every fish sample of each region. Heptachlor concentration was determined as 0.0598 μg/g in Dicentrarchus labrax sample from Marmara Sea, which is nearly nine thousand times more than the maximum allowable concentration of environmental quality standards biota of heptachlor listed in 2013/39/EU. The results show an indication of the significant health risks associated with the consumption of these contaminated fish in the Aegean and Marmara seas. In the Turkish food codex and in the 2013/39/EU directive, some heavy metals that do not have the maximum allowable concentration limits should be urgently indicated.